1999
DOI: 10.1111/j.1744-6570.1999.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies of Situational Tests

Abstract: In the present paper, results are reported for two different situational judgment tests (SJT) used in validation studies with almost 4,000 employees in 7 different organizations. Across the 2 studies, it was shown that situational test scores were significantly related to performance (weighted average T = .19), cognitive ability (weighted average T = .45), and experience (weighted average r = .20). In one study, there was a slight tendency for experience and cognitive ability to interact in the prediction of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 50 publications
5
117
0
12
Order By: Relevance
“…Such factor analytic SJT research typically reveals a plethora of factors that are difficult to interpret (Schmitt and Chan, 2006). This is not surprising as SJTs are measurement methods which assess a variety of work-related knowledge, skills, and abilities (KSAs) McDaniel and Whetzel, 2005;Weekley and Jones, 1999). For instance, SJTs were recently developed to capture domains as diverse as teamwork knowledge (McClough and Rogelberg, 2003;Morgeson et al, 2005;Stevens and Campion, 1999), aviation pilot judgment (Hunter, 2003), employee integrity (Becker, 2005), call-centre performance (Konradt et al, 2003), or academic performance (Oswald et al, 2004).…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such factor analytic SJT research typically reveals a plethora of factors that are difficult to interpret (Schmitt and Chan, 2006). This is not surprising as SJTs are measurement methods which assess a variety of work-related knowledge, skills, and abilities (KSAs) McDaniel and Whetzel, 2005;Weekley and Jones, 1999). For instance, SJTs were recently developed to capture domains as diverse as teamwork knowledge (McClough and Rogelberg, 2003;Morgeson et al, 2005;Stevens and Campion, 1999), aviation pilot judgment (Hunter, 2003), employee integrity (Becker, 2005), call-centre performance (Konradt et al, 2003), or academic performance (Oswald et al, 2004).…”
Section: Reliabilitymentioning
confidence: 99%
“…Another example is that SJTs based on a job analysis were usually more highly related to cognitive ability than those not based on a job analysis (0.50 versus 0.38). Still other researchers posit that SJTs are alternative measures of job knowledge, job experience or interpersonal variables (McDaniel and Nguyen, 2001;Weekley and Jones, 1999).…”
Section: Construct-related Validitymentioning
confidence: 99%
“…As with selection procedures, such as biodata inventories, structured interviews, and assessment center exercises, SJTs are best thought of as a method (rather than a specific construct) that can be used to assess a wide range of predictor constructs (Arthur & Villado, in press;Schmitt & Chan, 2006). Furthermore, situational tests are thought to capture declarative and procedural knowledge relevant to the target construct or constructs (Motowidlo, Hanson, & Crafts, 1997;Ployhart & Ehrhart, 2003;Weekley & Jones, 1999). Given these findings, a SJT would seem to provide a useful method for assessing one's knowledge concerning the variety of roles that individuals can choose in a team situation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence that the constructs SJTs assess are valid predictors of job performance (McDaniel, Morgeson, Finnegan, Campion, & Braverman, 2001) and that they tend to produce smaller ethnic group differences (Weekley & Jones, 1999) and more favorable applicant reactions (Bauer & Truxillo, 2006) than do cognitive ability tests. Although prior research has demonstrated the validity of KSA-based situational tests in team environments (Morgeson et al, 2005;Stevens & Campion, 1994), the present study is the first we know of that used a situational approach to measure team role knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…O que parece ser uma concordância na literatura é que os TJS são importantes devido a sua capacidade pre ditora do comportamento humano para a situação exposta (Hanson & Ramos, 1996;McDaniel, Morgeson, Finnegan, Campion, & Braverman, 2001;Phillips, 1992Phillips, , 1993Weekley & Jones, 1997, 1999. Esse compor tamento, entretanto, pode ou não estar relacionado a processos de seleção, ao ambiente de trabalho e, além disso, pode ou não ser aquele que seria assumido pelo indivíduo avaliado, conforme já visto no que tange às instruções de respostas.…”
Section: Formatos Dos Testes De Julgamento Situacionalunclassified